Hello j'ai besoin d'aide s'il vous plait pour le c) du 55 et le 56 Entier merci :)

2
ex 55
p = 5/18 ; m = 1/9 et n = 2/3
a)
m+n = 1/9+2/3
m+n = 1/9+6/9
m+n = 7/9

b)
p-m = 5/18-1/9
p-m = 5/18-2/18
p-m = 3/18
p-m = 1/6

c)
np = 5/18 x 2/3
np = 10/54

Ex 56
m = 3/4 ; n = 11/8 et p = 53/24
a)
p-(m+n) = 53/24-(3/4+11/8)
p-(m+n) = 53/24-(6/8+11/8)
p-(m+n) = 53/24-17/8
p-(m+n) = 53/24-17x3/(8x3)
p-(m+n) = 53/24- 51/24
p-(m+n) = 2/24
p-(m+n)

Réponses

Meilleure réponse !
2014-05-20T19:25:11+02:00
55)
a) m + n
= 1/9 + 2/3
= 1/9 + 2 x 3 / 3 x 3
= 1/9 + 6/9
= 7/9

b) p - m
= 5/18 - 1/9
= 5/18 - 1 x 2 / 9 x 2
= 5/18 - 2/18
= 3/18
= 3 x 1 / 3 x 6
= 1/6

c) np
= 2/3 x 5/18
= 6/54
= 6 x 1 / 6 x 9
= 1/54

56)
a) p - (m + n)
= 53/24 - (3/4 + 11/8)
= 53/24 - (3 x 2 / 4 x 2 + 11/8)
= 53/24 - (6/8 + 11/8)
= 53/24 - (17/8)
= 53/24 - 17 x 3 / 8 x 3
= 53/24 - 51/24
= 2/24
= 2 x 1 / 2 x 12
= 1/12

b) 2n + p
= 2 x 11/8 + 53/24
= 22/8 + 53/24
= 22 x 3 / 8 x 3 + 53/24
= 66/24 + 53/24
= 119/24

2014-05-20T19:33:28+02:00
ex 55
p = 5/18 ; m = 1/9 et n = 2/3
a)
m+n = 1/9+2/3
m+n = 1/9+6/9
m+n = 7/9

b)
p-m = 5/18-1/9
p-m = 5/18-2/18
p-m = 3/18 
p-m = 1/6

c)
np = 5/18 x 2/3
np = 10/54

Ex 56
m = 3/4 ; n = 11/8 et p = 53/24
a)
p-(m+n) = 53/24-(3/4+11/8)
p-(m+n) = 53/24-(6/8+11/8)
p-(m+n) = 53/24-17/8
p-(m+n) = 53/24-17x3/(8x3)
p-(m+n) = 53/24- 51/24
p-(m+n) = 2/24
p-(m+n) = 1/12

b)
2n+p = 2x11/8+53/24
2n+p = 22x3/(8x3) + 53/24
2n+p = 66/24+53/24
2n+p = 119/24